Implementation of the Correctional System For Inmates In Class I Correctional Institution Medan - Ali Adnan, Muhammad; Siringo Ringo, Gideon; Sunarto, Atika (Dinasti Research, 2024)
The correctional system is an important component in the framework of the integrated criminal justice system in Indonesia. This institution has strategic duties and responsibilities in enforcing the law and providing guidance to prisoners, correctional students, and correctional inmates at the pre-adjudication, adjudication, and post-adjudication stages. The implementation of the penitentiary system in Indonesia is based on the noble values ??of Pancasila and the state constitution, which upholds the principles of legal protection and respect for human rights. However, the implementation of the correctional system in many correctional institutions in Indonesia still faces various obstacles and problems. One of the crucial issues that often arises is the problem of overcrowding or excess housing capacity in correctional institutions. This condition not only gives rise to various technical and security problems but also hampers development and rehabilitation efforts for prisoners. This research aims to examine in depth three main aspects related to the penitentiary system in Indonesia. First, this research will analyze the legal basis and statutory regulations governing the correctional system, starting from constitutional norms to operational technical regulations. Second, this research will explore various efforts and strategies carried out by correctional institutions, especially the Medan Class I Correctional Institution, in overcoming the problem of overcrowding and optimizing the implementation of Law Number 22 of 2022 concerning Corrections. Third, this research will comprehensively analyze how the law is implemented in the practice of coaching and mentoring prisoners at the Medan Class I Penitentiary. The research method used in this study is an empirical juridical research method, which combines normative studies of statutory regulations with direct observation and interviews in the field. This research is descriptive-analytic, which means that the data and information obtained will be analyzed in depth concerning the applicable legal framework. The research results show that legal regulations regarding the penitentiary system in Indonesia are rooted in higher legal norms, namely Pancasila and the 1945 Constitution, which are then revealed in various statutory regulations, including Law Number 22 of 2022 concerning Corrections. To overcome the problem of overcrowding at the Medan Class I Correctional Institution, the institution has made various efforts, such as optimizing the social reintegration program, transferring prisoners to other correctional institutions that have more adequate capacity, and collaborating with various related parties. Implementation of Law Number 22 of 2022 concerning Corrections in Class I Medan Penitentiary covers various aspects, starting from fulfilling the rights and obligations of prisoners, implementing coaching and mentoring programs, as well as implementing a security system that is under applicable security standards. Even though there are still several obstacles in its implementation, the institution continues to strive to improve and improve the quality of the implementation of the correctional system to achieve the goals of law enforcement and justice.